Effect of Lactobacillus plantarum KFY02 isolated from naturally fermented yogurt on the weight loss in mice with high-fat diet-induced obesity via PPAR-α/γ signaling pathway. (December 2020) - Mu, Jianfei; Zhang, Jing; Zhou, Xianrong; Zalan, Zsolt; Hegyi, Ferenc; Takács, Krisztina; Ibrahim, Amel; Awad, Sameh; Wu, Yun; Zhao, Xin; Du, Muying
Graphical abstract: Highlights: Lactobacillus plantarum KFY02 was newly isolated from the naturally fermented milk yogurt in Korla of Xinjiang. The study used a high-fat diet (HFD) to induce obese mice. The normal group was fed 10% fat diet, and the other groups were fed 45% HFD. Observation of pathological changes showed that LP-KFY02 could alleviate the damage caused by obesity on the tissue samples from the liver of mice and reduce the expansion of fat cells. The results of qPCR and western blot experiments further showed that LP-KFY02 could effectively up-regulate the mRNA and protein expression of LPL, PPAR-α, CYP7A1 and CPT1A in the liver and epididymal adipose tissues, as well as cut down the mRNA and protein expression of PPAR-γ and C/EBP-α. LP-KFY02 could effectively treat obesity arose from HFD, and its effect is comparable to commercially available L-carnitine, and superior to the Lactobacillus delbruechii subsp. bulgaricus commonly used in industry. Abstract: In this study, an in vivo lipid-lowering animal experiment was performed on Lactobacillus plantarum KFY02 (LP-KFY02) newly isolated from Xinjiang fermented yogurt. The study used a high-fat diet (HFD) to induce obese mice. Serum and tissue samples from mice were examined by molecular biological detection. The results indicated that LP-KFY02 could inhibit increases in various organ indexes of mice caused by HFD. LP-KFY02 could reduce the levels of alkaline phosphatase (AKP), alanine aminotransferase (ALT), aspartate aminotransferase (AST), triglyceride (TG), total cholesterol (TC), and low-density lipoprotein cholesterol (LDL-c) in the serum and liver of obese mice with HFD and improve high-density lipoprotein cholesterol (HDL-C) levels. Observation of pathological changes also showed that LP-KFY02 could alleviate the damage caused by obesity on the tissue samples from the liver of mice and reduce the expansion of fat cells. The results of qPCR experiments further showed that LP-KFY02 could effectively up-regulate the mRNA expression of lipoprotein lipase (LPL), peroxisome proliferative-activating receptor α (PPAR-α), cholesterol 7α-hydroxylase (CYP7A1), and carnitine palmitoyltransferase 1A (CPT1A) in the liver and epididymal adipose tissues, as well as cut down the mRNA expression of peroxisome proliferative-activating receptor γ (PPAR-γ) and CCAAT enhancer-binding proteins (C/EBP-α). Furthermore, ELISA results showed LP-KFY02 obviously decreased the level of pro-inflammatory factors interleukin (IL)-6, TNF-α, IL-1β and IFN-γ in serum, but increased the anti-inflammatory factors IL-4 and IL-10 content. LP-KFY02 could effectively treat obesity arose from HFD, and its effect is comparable to commercially available L-carnitine, and superior to the Lactobacillus delbruechii subsp . bulgaricus commonly used in industry. LP-KFY02 is a health beneficial strain with probiotic potential.